Investigação, simulação e diagnósticos sobre o controle de acionamento de uma bobinadeira de aço inoxidável - Igor Barros Mairinck (2014)
This work consists of the study and the proposition of a solution of a real problem on speed and current limitation in the control loops of a steel cutting line. The actual system has nonlinear characteristics during operation due to variations of the system inertia, the radius of the coil and the resistant torque. The control performance directly affects the quality of the rolled product. Identification and modeling techniques of dynamical systems were used for the tuning of the control loops of the plant. This was performed using the MATLAB, PSPICE and PSIM tools. An analysis was done of the whole process. The study was focused on the control of the DC motors, lifting parameters and drive models and evaluating to possibility of improve the performance of control loops. Despite the importance of the effective control of this system, there are very few studies in the literature of the performance of control techniques for steel winding. This work presents the modeling, simulation and a proposed of tangential speed controller to a steel strip unwinding line, using classic (linear frequency domain) control technique. Simulations using a real process data show effectiveness of the control approach proposed in this work.